Prioritizing Positivity, Styles of Rumination, Coping Strategies, and Posttraumatic Growth: Examining Their Patterns and Correlations in a Prospective Study - Zięba, Mariusz; Wiecheć, Katarzyna; Wójcik, Natalia E.; Zięba, Michał J. (Frontiers in Psychology, 2022)
Objectives: A growing number of researches indicate that coping with the experience of a crisis event, which causes a breach in the individual's fundamental beliefs regarding the world and his/her place in it, can result in posttraumatic growth. Positive emotions can have an undoing effect on negative emotional arousal and broaden an individual's scope of action, and they can foster posttraumatic growth. This study aimed to examine relations between prioritizing positivity, styles of rumination, coping strategies, and posttraumatic growth. Methods: One hundred and sixty-four Polish adults took part in the study, filling out questionnaires to measure prioritizing positivity, hope and self-efficacy. Twelve-fifteen months later, 104 of them accepted the invitation to the second part of the study. The participants reported the intensity of rumination associated with the most critical event in their lives, which took place between the first and second stages of the study and the coping strategies they used. Posttraumatic growth and life satisfaction were also measured. Results: Results from hierarchical regressions found that higher levels of prioritizing positivity, deliberate ruminations, and religious coping and lower level of intrusive ruminations were associated with posttraumatic growth. The results also indicate that self-esteem was a significant predictor of life satisfaction. Conclusions: The results of the presented prospective study confirm that individual differences in prioritizing positivity can relate to a process of posttraumatic growth. Prioritizing positivity turned out to be associated with the use of adaptive coping strategies and deliberate but not intrusive ruminations. Previous studies on the role of prioritizing positivity have focused on the impact of seeking positive emotions in everyday life on the level of well-being. Our results show the importance of prioritizing positivity in coping with stress and trauma. These results can be used to design effective psychological intervention techniques to support people experiencing trauma and psychological crisis. The results also indicate that life satisfaction had different predictors than posttraumatic growth.